Development of Solar Photovoltaic Monitoring System For Maximum Power Point Tracking Solar Charge Controller - Nur Elya Maisarah Zulkifli; Farahiyah Mustafa; Nor Aira Zambri; Sim Sy Yi (Progress in Engineering Application and Technology, 2022)
Renewable energy is very important these days because it contributes significantly to the improvement of our climate. Renewable energy created very little environmental damage because it was derived from natural resources that replenished themselves in less than a human lifetime without depleting the planet’s resources. The proposed system refers to the online display of solar energy power usage as a renewable energy. For this study, the monitoring system is carried out on a Raspberry Pi with the Flask framework. The goals of this study are to observe the power extraction from the solar panel and to develop a monitoring system for the MPPT charge controller. As a result, this smart monitoring are going to display the daily usage of power extracted by the MPPT. This study will aid in the introduction of a concept of monitoring utilizing the online platform technique for improved display for the charge controller.